Evidence of air pollution exposure and new asthma onset: further justification for cleaner air. Issue 6 (3rd June 2021) - Thurston, George D.; Lee, Alison
The relationship between air pollution and health is being questioned by some, and the cost of further progress increases as the ambient levels decline, so it is important to document all the health benefits associated with cleaner air. It is well-established in the medical literature that exposure to outdoor air pollution is associated with multiple adverse health outcomes in adults [1–3]. But, in practice, we are largely restricted to "looking under the lamppost" of published studies of a limited list of routinely documented acute health outcomes (such as daily hospital admissions and death counts) in quantifying the health impacts of air pollution, and are therefore prevented from considering the full range of health benefits from cleaner air and their fiscal valuations to society. Indeed, the regulatory cost–benefit process usually does not account for any effects of air pollution on increased incidence of new disease, including asthma. Compared to the human health cost of acutely exacerbating a pre-existing lung or heart disease due to air pollution exposure, the long-term financial valuation of a new onset disease such as asthma is much greater from a public health standpoint, because initiation of chronic disease entails many years of diminished capacity, medical treatments, and lowered productivity. Further evidence that new onset asthma can occur from air pollution, even below prevailing air quality standards. It is time the ERS and ATS release a formal statement on the evidence for the link between long-term air pollution and new incident asthma. https://bit.ly/30uAjNN